Effi cacy of Allopatric Tephrosia Vogelii (Fabales: Fabaceae) against Pre-Emerginal Stages of Phlebotomus (Phlebotomus) Duboscqi (Diptera: Psychodidae) - Nathan M Aritho; Paul K Ndungu; Judith Inyangala; Milkah Mwangi; Michael M Gicheru; Joseph JN Ngeranwa; Christopher O Anjili (Open Journal of Plant Science - Peertechz Publications, 2017)
The effi cacy of allopatric Tephrosia vogelii in killing eggs and larvae of the sand fl y Phlebotomus duboscqi was tested in the laboratory. In this study effects of both water and crude powder extracs of Tephrosia vogelii were tested against against pre-emerginal stages of P. duboscqi in the laboratory. Three groups of eggs were wetted with T. vogelii extracts from Kilifi (TVK), Nairobi (TVN) and Vihiga Counties (TVV) and observed for morphological changes, motility, transformation and death. Six groups of 30 first instar larvae were fed on T. vogelii crude powder either alone or mixed with larvae food. All larvae given TVN powder become immortile, did not feed and died at the fi rst instar stage, whereas those fed on TVV and TVK did not die. Combining all the three extracts also led the death of all fi rst and second instar larvae, but gradual death and disintegration of third instar larvae was sequentially observed. The differences in activities of the allopatric plants can be attributed to allopatric introgression arising from geopgraphic separation leading to introgressive hybridization. The killing and anti-feedant activities of TVN could also mean that it is a chemotype 1 plant that contains rotenoid whereas TVK and TVV are chemotype 2 that lack rotenoids. Feeding deterrence has been shown to be caused by rutin and quercetin. Considering that only leaves were used, the toxicity of TVN can be attributed to single or combination actions of rotenone, elliptone, deguelin, rutin, rotenolone, tephrosin or quercetin that have been shown to be present in leaves. Results of this study suggest that T. vogelli has detrimental insecticidal effects on pre-emerginal stages of P. duboscqi and has potential for sand fl y control. This control method can be achieved through direct introduction of crude dried T. vogelii powder into termite mound ventilation shafts and animal burrows where sand fl ies are known to breed and rest.